2021
DOI: 10.3389/fpsyg.2021.616664
|View full text |Cite
|
Sign up to set email alerts
|

Mutual (Mis)understanding: Reframing Autistic Pragmatic “Impairments” Using Relevance Theory

Abstract: A central diagnostic and anecdotal feature of autism is difficulty with social communication. We take the position that communication is a two-way, intersubjective phenomenon—as described by the double empathy problem—and offer up relevance theory (a cognitive account of utterance interpretation) as a means of explaining such communication difficulties. Based on a set of proposed heuristics for successful and rapid interpretation of intended meaning, relevance theory positions communication as contingent on sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 91 publications
(124 reference statements)
2
26
0
Order By: Relevance
“…For instance, a conversational AI implemented for a playful environment would typically demand a different interaction style than one which is put to use in a crisis or emergency context (Goetz et al, 2003 ). Likewise, a conversational AI may have to adjust its behavior depending on whether it addresses a child or an adult, or a person with specific communicative deficiencies (Williams et al, 2021 ). Adaptation of its personality to the personality of the interlocutor could also increase conversational quality by exploiting the mechanics behind similarity-attraction, as indeed people have been shown that people feel more attraction toward people or systems that match their personality (Lee and Nass, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a conversational AI implemented for a playful environment would typically demand a different interaction style than one which is put to use in a crisis or emergency context (Goetz et al, 2003 ). Likewise, a conversational AI may have to adjust its behavior depending on whether it addresses a child or an adult, or a person with specific communicative deficiencies (Williams et al, 2021 ). Adaptation of its personality to the personality of the interlocutor could also increase conversational quality by exploiting the mechanics behind similarity-attraction, as indeed people have been shown that people feel more attraction toward people or systems that match their personality (Lee and Nass, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first, quantitative study was a sub-study of the ADIE clinical trial and includes data collected pre-intervention at the baseline assessment only. The second, qualitative study was a sub-study of the 'Talking Together' community engagement project Williams et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…This theory is largely at odds with reports from the autistic community of a longing for improved social connection (Causton-Theoharis et al, 2009), and has been criticized on this basis (Jaswal & Akhtar, 2019). A discrepancy in mutual understanding between autistic and non-autistic individuals, rather than an autistic deficit in social motivation, provides a more valid framework for appraising communication difficulties and associated feelings of loneliness (Milton & Bracher, 2013;Milton et al, 2018;Milton, 2012;Williams et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Autistic people tend to have to change to suit other people's communication styles (Williams et al, 2021). Ensuring the social engagement of communication is put upon the autistic person, terming them as "socially disabled."…”
Section: Considering the Double Empathy Problem: Autistic Socialitymentioning
confidence: 99%